Use of High-intensity Focused Ultrasound in the Management of Extra-abdominal Desmoid Tumors - Bartocci, Margherita; Bazzocchi, Alberto; Napoli, Alessandro; Ghanouni, Pejman; Spinnato, Paolo; Facchini, Giancarlo; Bonomo, Lorenzo; Albisinni, Ugo (Current Medical Imaging, 2018)
Background: High-intensity focused ultrasound ablation is an emerging mode of therapy for benign and malignant neoplastic processes; with respect to musculoskeletal tumors, high-intensity focused ultrasound ablation has been used for palliative treatment of bone metastases and primary treatment of osteoid osteoma, synovial sarcoma, osteosarcoma, Ewing sarcoma, chondrosarcoma and giant cell bone cancer. However, very little has been reported on its use on soft tissue tumors including extra-abdominal desmoids. Objective: We provide an overview of studies assessing the efficacy of high-intensity focused ultrasound ablation for extra-abdominal desmoids and its potential future applications. Methods: A review of the literature was conducted using the keywords “desmoid” and “focused ultrasound”; articles, which provided interpretable data about the treatment of this pathological condition using high-intensity focused ultrasound, were identified. Results: Experience with high-intensity focused ultrasound ablation of extra-abdominal desmoids is limited and in particular it has been reported by Wang et al. in 2011 and by Avedian et al. in 2015. According to these research groups, high-intensity focused ultrasound is a safe and effective non-invasive therapeutic modality in the treatment of desmoid tumors. Conclusion: High-intensity focused ultrasound may be useful to treat soft tissue tumors of extremities, especially in situations in which standard treatments would be associated with unacceptable morbidity as is often the case with extra-abdominal desmoids.
Keywords: High-intensity